Navigating the Transition to Rooftop Solar in an Islanded Electricity System: a Western Australian Case Study - Wilkinson, Sam (Curtin University, 2021)
Sam's thesis answers the question of: which transition factors should be focused on to ensure a stable electricity supply as we shift from thermal coal and gas to a solar PV dominant electricity system. His thesis identifies technical and market challenges to be addressed and finds that it is helpful to first understand the lock-in mechanisms affecting transition pathways and how to engage electricity users in the required change processes.